SURVEYS MEASUREMENT OF PUBLIC OPINION BETWEEN THEORY AND PRACTICE - Najem Abdulaa, Suhail; Saad , Ali Muat; Muhamad Al-Bayaa, Mahdi (ALBAHITH ALALAMI, 2022)
The majority of statisticians, if not most of them, are primarily concerned with the theoretical aspects of their field of work rather than their application to the practical aspects. Its importance as well as its direct impact on the development of various sciences. Although the theoretical aspect is the first and decisive basis in determining the degree of accuracy of any research work, we always emphasize the importance of the applied aspects that are clear to everyone, as well as its direct impact on the development of different sciences. The measurements of public opinion is one of the most important aspects of the application of statistics, which has taken today, a global resonance and has become a global language that everyone can have access to and benefit from it. We do not exaggerate when using the word “Language”, because here we mean the language of numbers, which is the most accurate of all words and phrases that can describe a situation, or explain a particular problem. This research is but a modest attempt to remind the importance of public opinion measurements and encourage it, especially Iraq today, where is the need for a strong base for measuring public opinion based on the correct scientific foundations. This research represents the results of our efforts in Iraq Center of Research and Strategic Studies for almost a year and a half, where we also faced delicate problems and details that accompany the studies of public opinion measurements, taking into account the specificity of Iraq today and the deteriorating security conditions. This research will also review the main findings of the Center in both the economic and social aspects that contributed to the development of Iraqi society. The research problem can be formulated with the following questions:What is the concept of measuring public opinion, and how is it measured ?What is the contribution of statistics in the applied aspects of Iraqi society ?Is it possible to apply the concept of measuring public opinion in Iraq ?The research aims to set a number of objectives as follows:Provide a modest academic framework on the concept and methodology of measuring public opinion.2- Determining the gap between the academic side of pure sciences (in particular, statistics) and the applied side of this science, which is the measurement of public opinion.Highlighting the mechanism of establishing specialized centers to measure public opinion.highlighting some important aspects in our Iraqi society, such as economic, social and political aspects.